AMINO ACID, PROTEIN, AND COLOR PROFILE OF SWEET CORN EXTRACT SUBSTITUTED WITH MORINGA LEAF EXTRACT - Widodo, Widodo; Cahyono Murti, Siti Tamaroh; Kanetro, Bayu (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Sweet corn (Zea mays saccharata) is a popular source of carbohydrates and dietary fiber but has a relatively low protein content. To increase its nutritional value and functional potential, substitution was carried out with Moringa oleifera leaf extract which is rich in essential amino acids and bioactive compounds. This study aims to evaluate the effect of Moringa leaf extract substitution on the amino acid profile and color characteristics of sweet corn extract. The study design was a Completely Randomized Design (CRD) with two treatments, namely substitution of the addition of Moringa leaf extract, young and old shoots, in the ratio of sweet corn extract and Moringa leaf extract (80:20; 85:15 and 90:10). The test on the research results was carried out on color, the color was carried out using a colorimeter with parameters L * (brightness), a * (red-green), and b * (yellow-blue), protein content. The amino acid profile test was selected on the best research results using high-performance liquid chromatography (HPLC). The data obtained were statistically tested using Analysis of Variance (ANOVA). If there was a significant difference between treatments, it was continued with the Duncan test (DMRT). The results showed that increasing the concentration of Moringa leaf extract significantly reduced the L * value and increased the a * value (p<0.05), indicating a more intense green color, without significant changes in the b * value. Meanwhile, the selected product for amino acid profile testing was in the treatment of 90:10 young leaf sweet corn extract, with high amino acids in aspartic acid (114.54 mg / L), glutamic acid (222.45 mg/L) and alanine (294.73 mg/L).